Tips dan Trik Penulisan Penelitian Tindakan Kelas di Lembata - Hendrik A.E. Lao; Ezra Tari; Lanny I.D. Koroh; Martin Ch. Liufeto; Hendrik Sodak (Abdimas Universal, 2022)
Classroom action training begins with the problem of teachers who are still minimal in writing. The service team found that many teachers had not been able to combine observations in class. This research is a way for teachers to research in the classroom to find problems in the learning process. The teacher found many problems related to learning, namely process design, media, learning techniques, and learning outcomes. To realize good classroom action research techniques, training is done. Some teachers have not been able to write a good scientific paper. So the service team trains skilled teachers in writing. The service method begins with team formation, formulation of goals, and communication with the head of the Ministry of Religion office, then the analysis of needs in the field, determination of solutions to service problems and implementation. This training produces groups of writer teachers according to their respective fields. The team found already teachers who made classroom action research, but difficult in pouring it into the article. So that the team assists in writing classroom action research articles that will be published in journals. Follow-up assistance is carried out in the Whatsapp Messenger group.